IBUPROFEN INJECTABLE MICROEMULSION PREPARATION COATED BY CHITOSAN: FORMULATION, CHARACTERIZATION, IN VITRO PERFORMANCE, ANTI-INFLAMMATION ACTIVITY, AND HEMATOLOGY ASSESSMENT - UL HAFIZAH, AULIA; SUGITA, PURWANTININGSIH; KHOTIB, MOHAMMAD; CAHYANINGSIH, UMI; SADIAH, SITI (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to develop, characterize, and conduct stability evaluations to ensure compliance with intravenous administration for microemulsion ibuprofen injection. In addition, hematology assessment and profile of drug release kinetics were analyzed. Methods: The formulation process commenced by introducing various chitosan concentrations into microemulsion ibuprofen injection, following a method established in a previous study. Formulation parameters studied include particle size, polydispersity index (PDI), zeta potential, kinetic of drug release, anti-inflammation activity using the 1% carrageenin induction method, and hematology assessment. Results: The results showed that the addition of 1% chitosan solution allowed for the development of the ideal microemulsion formula, with droplet size, zeta potential, and PDI of 19.37±0.32 nm,-1.53±0.12 mV, and 0.38±0.02, respectively. Kinetics of chitosan-coated ibuprofen microemulsion (MK) were governed by the squared root of time paradigm, suggesting that drug release proceeded by diffusion and was influenced by the carrier. Compared to the other groups, the paw injected with MK indicated a strong anti-inflammatory effect and did not differ significantly from the control group (p>0.05). However, Hematology analysis showed no statistically significant variations in leukocyte and erythrocyte profiles between the treatment and control groups (p>0.05). Conclusion: MK met the criteria as an intravenous preparation based on the characteristics and safety.